Compostagem de resíduos de alimentos e podas trituradas de árvores em leiras estáticas como mecanismo de redução de GEE - Veras, Roani Simões (2018)
The passively aerated windrowe composting method has advantages in terms of operational simplicity and cost reduction due to the fact that there is no need of stirring and reduction of greenhouse gas emissions. This paperwork objective was the co mparison of two different composting methods in a period of 135 days: turned windrow composting and passively aerated windrowe . It was used food wastes from the local restaurants in the universtiy and tree pruning from Fortaleza urban area. The following p arameters were analyzed: temperature, moisture, pH, C/N ratio, electrical conductivity, seed germination index and mass balance. The O 2 , CO 2 and CH 4 gases composition in the active degradation phase was monitored for a specific static pile (EP100). A total of 12 windrows were installed with heights of 0,50 m, 0,75 m and 1,00 m; with two different types of operation: stirred (R) and static (E); and two forms of assembly, premixed (P) and alternate layers (C). The EP100 windrow stood out from the others teste d because it was the only one to reach the temperature and period within the hygiene standard established by the recent CONAMA 481/2017. This treatment method also met the parameters of Normative Instruction 25/2009 of the Ministry of Agriculture, Livestoc k and Supply, with the exception of moisture. On the other hand, the static piles assembled in alternate layers (ECs) have not met the quality standards for temperature, humidity and seed germination index. The EPs and RPs presented mass reduction above 7 5% on a dry basis. Regarding the EP100 gases monitoring , the oxygen gas concentration remained above 15% and there was no detection of methane gas. According to the results, the passively aerated windrowe composting for heights of 1.00 m and conditions est ablished in the paper work have shown its efficiency . This method is indicated for organic waste t reatment in small and large communities.